Institutional settings for networking in Poland - Stanislaw Walukiewicz; Barbara Szymoniuk (European Regional Science Association (ERSA), 2002)
We consider institutional settings for networking in the context of innovative regional strategy development. Several examples of such institutions will be given and then conclusions and recommendations will be formulated emphasizing the pre-accession context. Poland completed the comprehensive reform of regional and local administration to have achieved a system similar to the system existing in the European Union. The system is based on the NUTS 2 size regions. Therefore, the competencies of the state and regional authorities to develop S/TD and Innovation infrastructure and policies in Poland are appropriate to the standards in the European Union. The paper will start with critical evaluation of the regional development policies recently presented by the regional self-governments in Poland. The overview of the implementation measures for these policies will be presented with an emphasis put on the pre-accession context. The second part of the contribution gives assumptions and general description of the Poland's National and Regional Innovation Systems that is substantially based on the findings of the Phare SCI-TECH II Programme concluded in 2000. The Centre for Industrial Management PAS took an active role in the implementation of this Programme. The analysis is based on the so-called 'Learning Regions', in which the role of dense inter-connetions between segments in the innovation systems comes into prominence.
Keywords: 330